Fanny Sadowski: una rivale della Ristori - Di Tizio, Raffaella (Drammaturgia, 2023)
This essay investigates the actress Fanny Sadowski, whose stile was opposite to that of Ristori and who was highly considered by her contemporaries. Her career is compared to that of Ristori starting from the portrait offered by Leone Fortis in the 1888 introduction to his Cuore ed arte, written in 1852 for Sadowski. Born a few years apart, both married to aristocrats, both died in 1906, they developed their careers in the opposite directions of a new internationalism (Ristori) and a stabilisation in a precise cultural context (Naples for Sadowski). This context, crossed by Ristori in three successive tours, is chosen to set in motion the canonical image of the actress-marquise, observing her in contrast to her rival, Queen of Naples as she was within and beyond Europe. The basis of this essay is the documentation collected for an entry on Sadowski for the Dizionario biografico degli italiani, combined with research in the Fondo Ristori in the Museo Biblioteca dell’Attore in Genoa, about direct and indirect encounters between the two actresses. Fanny Sadowski, whose style would mirror in Eleonora Duse, reveals to be an important actress of her time, capable of exerting profound and lasting influences.